PENDIDIKAN AGAMA ISLAM DAN PENDIDIKAN ISLAM TINJAUAN EPISTEMOLOGI, ISI, DAN MATERI - Mahmudi Mahmudi (Universitas Islam Sultan Agung, 2019)
This paper presents two terms which have differences, namely Islamic religious education and Islamic education. To see these two terms, the author reviews them from two interrelated aspects, namely the epistemological aspect as the theory of knowledge and aspects of content or material which is one of the important points in understanding the curriculum. Meanwhile, in terms of epistemology, Religious Education is more inclined to apply in educating in the context of Islam. While Islamic education speaks at the source level, in theory, the principle recorded is the forerunner of the Islamic Religious Education material itself. As for content or material, basically between Islamic Education with Islamic education as in an epistemological view, there is no difference which means that the terms contained in Islamic Education include aqidah, worship, and morals which are explained in terms of an introduction to Allah SWT, potential, human functions, and morals. Keywords: Education, Islamic Education, Epistemology This paper presents two terms which have differences, namely Islamic religious education and Islamic education. To see these two terms, the author reviews them from two interrelated aspects, namely the epistemological aspect as the theory of knowledge and aspects of content or material which is one of the important points in understanding the curriculum. Meanwhile in terms of epistemology, Religious Education is more inclined to apply in educating in the context of Islam. While Islamic education speaks at the source level, in theory, the principle recorded is the forerunner of the Islamic Religious Education material itself. As for content or material, basically between Islamic Education with Islamic education as in an epistemological view, there is no difference which means that the terms contained in Islamic Education include aqidah, worship, and morals which are explained in terms of introduction to Allah SWT, potential, human functions, and morals. Keywords: Education, Islamic Education, Epistemology